(untitled) (Research, Society and Development, 2021)
With the declaration of the new Coronavirus pandemic (COVID-19) by the World Health Organization (WHO), onMarch 11, 2020, the escalation by research on possible strategies for its confrontation has reached a new level. The objective of this study was to evaluate the coverage of health insurance companies in relation to COVID-19 tests determined by the National Supplementary Health Agency (ANS) and to analyze the number of COVID-19 tests performed in Brazil. This is a documentary, ecological study, which was carried out from March 2020 to March 2021. The data released by the National Supplementary Health Agency was verified in relation to the tests included in the List of Procedures and Events in Health of ANS. In the state health departments, the number of tests performed daily in Brazil was analyzed. During this period 07 tests were implemented by ANS: SARS-CoV-2 (CORONAVIRUS COVID-19) - RT search - PCR (with usage guidelines), D-Dimer (dosage), Procalcitonin (dosage), Research tests rapid for Influenza A and B, and real-time PCR for Influenza A and B viruses in addition to the Quick Search tests for Respiratory Syncytial Virus and real-time PCR for Respiratory Syncytial Virus. The Southeast region carried out the largest number of tests in Brazil, with almost 50% of the total, followed by the Northeast region, which tested approximately 25% of the inhabitants. The types of tests determined by the ANS are in accordance with the recommendations of the Ministry of Health of Brazil, however, it is concluded that some health plan operators are not following the determination of the ANS in relation to the coverage of these tests, negatively influencing the number of tests carried out in the country.